Karakter Toleransi: Pembelajaran PKN Berbasis Model Kooperatif Tipe Think Pair Share (TPS) MI NU Miftahul Ulum - Laana Nafisatus Suroyya (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
Encourages students to work in groups to find answers to questions based on concepts, the think pair share (TPS) approach is one of the instructional strategies that must be employed in teaching and learning activities. The low learning outcomes of students is one of the issues with PKn learning. This is because while lecturing and Q&A sessions are the most common teaching and learning methods used in classrooms, students' ability to ask questions and seek assistance from lecturers is still insufficient. This study aims to explain the TPS concept and its application to PKn learning in elementary schools. Cooperative learning approach using a contextual learning model (TPS) One of the most useful learning models for raising student response and learning results, particularly in PKn learning, is Think Pair Share.